Evaluating technology integration in a Vietnamese university language program. Issue 5 (4th July 2019) - Gruba, Paul; Chau Nguyen, Ngoc Bao
Abstract: In the main, evaluation in CALL has focused on the assessment of the individual use of technology in accord with the principles of second language acquisition. Now that CALL focuses on the full integration of technology in language programs, evaluators are urged to take into account a wide range of factors that span institutional policy, departmental culture and classroom practice. In this study, we use an argument-based approach to evaluate technology integration within an English language program at a leading university in Vietnam. Using a layered approach and qualitative techniques to gather data, we examine how administrators and lecturers at the departmental, or meso, level perceive technology integration in an English language program. Results of the study inform technology integration, stakeholder identification, resource allocation and curriculum interpretation, and concludes with a discussion of the utility of blended language program evaluation.